(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2015)
A protocol was developed to produce large amount of callus in short a period of time from leaf explants of Stevia rebaudiana Bert. The highest amount of white callus was obtained on MS medium supplemented with 2.5 mg/l 2, 4-D and 0.5 mg/l BAP after 3 weeks of inoculating leaf segments. On the other hand, 0.5 mg/l BAP and 1.0 mg/l Kn exhibits poor performance towards callus formation while after using 1.0 mg/l Kn alone did not develop any callus. In this experiment, highest amount of green callus was obtained when MS medium supplemented with 2.5 mg/l NAA and 10% coconut water was used. An improved analytical method HPLC was applied to analyze stevioside extracted from the leaf and callus of Stevia rebaudiana. The stevioside in each sample were analyzed by comparing their retention times with those of the standards. The retention time (RT) of stevioside for leaves were found 14.96 and for callus 13.81 mins. The percentage of stevioside content from leaves and callus was 12.19% and 12.62% respectively DOI: http://dx.doi.org/10.3329/bjsir.v49i4.22621 Bangladesh J. Sci. Ind. Res. 49(4), 199-204, 2014